REPRESENTATION OF SPIRITUAL VALUES IN NUSSA DAN RARA ANIMATION AND ITS RELEVANCE TO ISLAMIC RELIGIOUS EDUCATION - Haqiqi, Sakinatul; Khumaidi, Ahmad; Ulfah, Yeniati (Qawwam : The Leader's Writing, 2025)
Amid the rapid flow of digitalization and the dominance of visual culture, Islamic Religious Education (PAI) faces strategic challenges in conveying spiritual values to the younger generation. Children growing up in digital ecosystems tend to be more responsive to emotional and visual narratives than to conventional verbal approaches. This study aims to analyze the representation of spiritual values in the animated series Nussa and Rara and to explore its relevance to Islamic education in the digital age. Employing a qualitative descriptive approach and content analysis method, this research examines selected episodes based on three main categories: worship, jihad (in its broader ethical sense), and exemplary character. The findings reveal that Nussa and Rara consistently deliver Islamic values through narrative, visual, and symbolic elements that align with the developmental psychology of children. These values are not delivered through instruction, but rather internalized through characters, everyday conflicts, and emotionally resonant resolutions. This study shows that animation can serve as an effective medium for strengthening religious attitudes, supporting the affective objectives of the Islamic education curriculum, and bridging learning spaces between school and home. Moreover, the series aligns with the principles of the Merdeka Curriculum, making it a relevant instrument for thematic, contextual, and character-based learning in contemporary Islamic education.